Functional Fcgamma Receptor Polymorphisms Are Associated with Human Allergy - Wu, Jianming; Lin, Rui; Huang, Jinhai; Guan, Weihua; Oetting, William S.; Sriramarao, P.; Blumenthal, Malcolm N. (PLOS ONE, 2014)
Objective IgG Fc receptors (FcγRs) play important roles in immune responses. It is not clear whether FcγR receptors play a role in human asthma and allergy. The aim of current study was to investigate whether functional single nucleotide polymorphisms (SNPs) of FcγR genes (FCGR) are associated with human asthma and allergy. Methods Functional SNPs of FCGR2A (FcγRIIA-131His>Arg, rs1801274), FCGR2B (FcγRIIB-187Ile>Thr, rs1050501), FCGR2C (FcγRIIC-13Gln>Stop, rs10917661), FCGR3A (FcγRIIIA-158Val>Phe, rs396991), and FCGR3B variants (FcγRIIIB NA1 and NA2) were genotyped in an asthma family cohort including 370 atopy positive, 239 atopy negative, and 169 asthma positive subjects. The genotype and phenotype data (asthma, bronchial hyper-responsiveness, and atopy) of subjects were analyzed using family-based association tests (FBAT) and logistic regression adjusted for age and sex. Result The FcγRIIA-131His>Arg SNP is significantly associated with atopy in a family-based association test (P = 0.00287) and in a logistic regression analysis (P = 0.0269, OR 0.732, 95% CI: 0.555–0.965). The FcγRIIA-131His (or rs1801274-A) allele capable of binding human IgG2 has a protective role against atopy. In addition, the rare FcγRIIB-187Thr (or rs1050501-C) allele defective for the receptor-mediated inhibitory signals is a risk factor for atopy (P = 0.0031, OR 1.758, 95% CI: 1.209–2.556) and IgE production (P<0.001). However, variants of activating FcγRIIIA (rs396991), and FcγRIIIB (NA1 and NA2), and FcγRIIC (rs10917661) are not associated with asthma, BHR, and atopy (P>0.05). Conclusions FcγRIIA and FcγRIIB functional polymorphisms may have a role in the pathogenesis of allergy.